The Role Of Investigators In The Application Of Restorative Justice And Rehabilitation To Victims Of Drug Abuse In The Belawan Port Police - Sirait, Mangatur; Kusbianto, Kusbianto; Sitompul, Ariman (Legalpreneur Journal, 2024)
This study aims to determine the application of restorative justice and rehabilitation in the case of narcotics crime in legislation, the role of investigators in implementing restorative justice and rehabilitation in the Belawan jurisdiction, as well as the obstacles faced by investigators in implementing restorative justice and rehabilitation in the region. The research method used in this study is empirical juridical research that combines elements of law and scientific method. This study uses a qualitative approach with data collection techniques through interviews and document studies. The data sources consist of primary data obtained through observation, interviews, and questionnaires, as well as secondary data derived from primary and secondary legal materials. Data analysis is done descriptively by grouping, interpreting, and summarizing the data obtained. Investigators have an important role in handling cases of victims of drug abuse, including in the investigation, investigation, and rehabilitation. The implementation of restorative justice and rehabilitation at the Belawan Port Police Station has been carried out, but there are still obstacles such as lack of knowledge and skills of investigators, lack of support and facilities, and lack of community involvement. Increased training for investigators and stronger cooperation with communities and rehabilitation institutions are needed to improve the effectiveness of Drug Abuse Prevention.